Brand Image, Service Quality, and Purchase Decisions: The Mediating Role of Promotional Programs - Oktaweno Orlando; Budi Haryono (Universitas Negeri Gorontalo, 2026)
Purpose: This study aims to analyze the effect of brand image and service quality on new motorcycle purchase decisions, with promotional programs serving as a mediating variable at PT WOM Finance Palu Branch. The study is motivated by fluctuations in new motorcycle financing demand, indicating that consumers' purchase decisions are influenced not only by economic considerations but also by marketing factors, including brand image, service quality, and promotional programs.Design/Methodology/Approach: This study employed a quantitative approach using an explanatory research design. Data were collected through a survey of 75 consumers selected using proportional sampling. The research instrument consisted of a structured questionnaire measured on a five-point Likert scale. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software to examine both direct and indirect relationships among the variables.Findings: The results indicate that brand image, service quality, and promotional programs have positive and significant effects on purchase decisions. Brand image and service quality also have positive and significant effects on promotional programs. Furthermore, promotional programs significantly mediate the relationship between brand image and purchase decisions, as well as between service quality and purchase decisions. These findings demonstrate that integrating a strong brand image, excellent service quality, and effective promotional strategies plays a crucial role in enhancing consumers' purchase decisions for new motorcycle financing.